DIABETIC PATIENTS AND INFECTION RISKS IN SUB-SAHARAN AFRICA: EVIDENCE FROM YAOUNDÉ CENTRAL HOSPITAL, CAMEROON - Emmanuel Nguemegne, Jean-Baptiste; Aissatou Mvogo, Marie-Claire; N. Tchoumi , Samuel; Sophie Ndong , Aline (American Research Journal of Nursing and Health Sciences (ARJNHS), 2024)
Diabetes mellitus, a global health crisis, contributes significantly to morbidity and premature mortality. While developed countries primarily face diabetes-related cardiovascular and renal complications, the situation in Africa is complicated by a high prevalence of infectious diseases, including tuberculosis, which exacerbates diabetes-related mortality. The global death rate attributable to diabetes is 11.3%, with Africa accounting for 6.8% of these deaths (IDF Diabetes Atlas, 2019). In the African context, diabetes often serves as a precursor to additional health challenges, amplifying its impact. Notably, in Cameroon, research has predominantly focused on mortality associated with acute metabolic complications, leaving a gap in understanding the combined burden of diabetes and infectious diseases. This study aims to address this gap by evaluating the burden of infection among diabetic patients in the sub-Saharan region, with a specific focus on Yaoundé Central Hospital in Cameroon. The findings highlight the intersection of diabetes and infectious diseases, providing insight into the complex health dynamics faced by diabetic patients in this region